2019
DOI: 10.1016/j.blre.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Flaming and fanning: The Spectrum of inflammatory influences in myelodysplastic syndromes

Abstract: The myelodysplastic syndromes (MDS) represent neoplasms derived from the expansion of mutated clonal hematopoietic cells which often demonstrate aberrant differentiation potential with resultant cytopenias and a propensity to evolve into acute myelogenous leukemia. While multiple mutations have been identified which may serve as drivers of the MDS clone, there is accumulating evidence that MDS clones and subclones are subject to modulation by the marrow microenvironment and its inflammatory milieu. There is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 149 publications
0
36
0
Order By: Relevance
“…Cell pyroptosis death is found to be a potential toxic effect of xenobiotic pollutants that results in over-activation of inflammation, tissue damage, even malignant tumors [1,6,27]. It was reported pyroptosis is a highly inflammatory form of programmed cell death drove by caspases activation accompanied with release of pro-inflammatory cytokines IL1β [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell pyroptosis death is found to be a potential toxic effect of xenobiotic pollutants that results in over-activation of inflammation, tissue damage, even malignant tumors [1,6,27]. It was reported pyroptosis is a highly inflammatory form of programmed cell death drove by caspases activation accompanied with release of pro-inflammatory cytokines IL1β [18].…”
Section: Discussionmentioning
confidence: 99%
“…Limit studies have shown that pyroptosis may be involved in multiple types of haematological diseases such as MDS and acute myelogenous leukemia (AML). For example, researcher found that pyroptotic and other cellular inflammatory mediators promoted progression of MDS [1]. Rodriguez-Cimadevilla JC, et al, has reported that IL1β can stimulate AML growth [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, sterile inflammation via NLRP3 inflammasome activation has been linked to LR MDS. Activation of NLRP3 triggered bone marrow inflammation, expansion of myeloid-derived suppressor cells in the bone marrow, and a higher rate of hematopoietic cell damage and cell death [ 105 , 106 ]. Since then, it has been widely accepted that NLRP3-driven pyroptosis, a caspase-1 dependent proinflammatory form of lytic cell death, is fundamental in MDS pathology.…”
Section: Aspects On Iron Hepcidin Inflammation and Mdsmentioning
confidence: 99%
“…Myelodysplastic syndromes (MDS) are characterized by ineffective hematopoiesis, leading to hematopoietic precursor cell apoptosis and peripheral blood cytopenia [1]. In MDS, cytogenetic aberrations play an important role in classi cation and prognostication.…”
Section: Introductionmentioning
confidence: 99%